Knowledge-based decision system for tractor-trailer selection in a plantation. - Bardaie, Mohd. Zohadie; Chan, Kah Whye (1990)
A knowledge-based decision system is a computer software system that is able to provide advice in a particular subject area equal in quality to that which could be provided by an acknowledged human expert. The system does not generate new knowledge. What it does is provide access to existing expert knowledge. However, that knowledge may well be new to the user of the computerised knowledge-based decision system, and here in lies its benefit. In this paper, a knowledge-based decision system is presented for the selection of tractor-trailer combination in an oil-palm plantation. The selection of field machinery is a complex due to some unique characteristics of the plantation sector compared with other industries. These characteristics include the fact that each plantation has many special local conditions ; production is seasonal ; need for timely operations in a plantation ; and the supply and ability of plantation labor is quite varied. These characteristics are taken into consideration when developing the knowledge-based system. An expert-system shell (VP-EXPERT) is used in the development. The system is linked to various external programs (written in TURBO PASCAL) and data-base, inorder to provide the knowledge required. A feature which has been incorporated into the system is the 'why' characteristic. This feature enables the system to explain its actions.